Anti-arrhythmic effect of total saponins of Panax notoginseng - LIU Sai; CHEN Jun-xiu (Acta Pharmacologica Sinica, 2016)
Total saponins were extracted from the root of Panax notoginseng (Burk) F H Chen. It showed anti-arrhythmic effects on (1) chloroform-induced ventricular fibrillation in mice; (2) BaCl2-or aconitine-induced arrhythmia in rats; (3) epinephrine-induced arrhythmia in tabbits under chloroform; (4) centricular fibrillation threshold of rabbits. It antagonized isoprenaline-induced tachycardia non-cometitively. The slowing of beart rate was not influenced by atropine. It inhibited the excitability, automaticity and contractility of isolated guinea pig atria. The lengthening of A-H interval in electrogram of His bundle indicated that A-V nodal conduction velocity was decreased.